MASERASI ALKALI DARI BATANG PISANG (Musa paradisiaca) MENGGUNAKAN PELARUT AQUADEST - Lilis Sukeksi; Patima Valentina Haloho; Masniar Sirait (Talenta Publisher (Universitas Sumatera Utara), 2017)
The purpose of this research is to determine the time of alkali absorption from banana stem in semibatch and batch. In this study maceration maseration is a leaching process used to obtain the time required for solvent to absorb alkali in banana stem ash. While the batch system maseration is a leaching process used to obtain the time required for the solvent to reach saturation point (stop absorbing). Data collection techniques in this research are: sample preparation and drying of banana stem, banana stalking process banana stem, brazing ash process of banana stem in semibatch and batch, and determination of alkaline content by titration method. From result of research can be concluded that banana stem potentially serve as source of alkali because potassium (K2O) and sodium (Na2O) content in banana ash sticks respectively 36,19% and 13,99%. Water content and yield of banana ash sticks were 78.6% and 17.7%, respectively. The time for the semibatch system is obtained in 72 hours, while for the batch system was obtained in 12 days. Normalities of alkali extracts in semibatch and batch maceration still increased. Where in the ratio of banana stem ash/solvent is 1 gram / 25 ml; 2 gram / 25 ml; 3 gram / 25 ml; and 4 gram / 25 ml respectively had a normality value that still increased from 0.219 N to 0.567 N; 0.407 N to 0.891 N; 0.578 N to 1,315 N; and 0.819 N to 1,345 N. The highest permeated alkali yield was obtained ratio (banana stem ash/ solvent) 1 gram / 25 ml of 52.37%.